Tajikistan - Autonomous Adaptation to Climate Change : Economic Opportunities and Institutional Constraints for Farming Households - World Bank (Washington, DC, 2014)
Climate change presents significant threats to sustainable poverty reduction in Tajikistan. The primary impacts on rural livelihoods are expected to stem from reduced water quantity and quality (affecting agriculture), and increased frequency and severity of disasters. Options for farming households to autonomously adapt (and thereby move from climate vulnerability to resilience) include adoption of on-farm and off-farm measures. Farmland restructuring and the promotion of innovative rural production and land management measures have the potential to incentivize productivity and sustainable practices and reduce vulnerability, but achieving these objectives will rest on the behavioral responses of beneficiaries. In this context, assessing existing practices, as well as understanding institutional constraints to adaptation is crucial to improving economic opportunities for Tajik households and reducing vulnerability through well-designed interventions. This note examines the role of institutional factors (land tenure, legal security, and gender agency) in autonomous adaptation and improved resilience of rural communities through strategies for coping with climate-related shocks, sustainable land management practices, and income diversification. The note analyzes the extent to which differences in land rights are associated with differences in adaptation strategies and outcomes. The study focuses on two of Tajikistan s four main administrative divisions: Khatlon and Sughd districts. This note relies on a survey of farming households and a qualitative study that were undertaken specifically for this analysis. The note is structured as follows: section one give introduction. Section two describes land tenure arrangements, gender-related constraints, and sustainable land management practices in Tajikistan. Section three discusses the shocks experienced by households and the coping strategies used (including on-farm and off-farm strategies). Section four analyzes the determinants of knowledge and adoption of sustainable land management practices and on-farm investment. Section five concludes with policy recommendations to enable effective climate change adaptation by farming households.